Wear behaviour of martensitic NiTi shape memory alloy under ball-on-disk sliding tests - Yan, Lina (2013)
Ball-on-disk sliding wear tests were conducted on martensitic NiTi shape memory alloy against an alumina counter ball. The wear features and coefficients of friction of the samples subjected to different loads and sliding cycles were investigated to reveal the degradation process of the NiTi surface. Three stages of degradation were identified, namely, a near-zero wear stage, a transition wear stage and an abrasive wear stage. A special wear feature, herein referred to as the “crown-like structure”, was produced under near-zero and transition wear conditions and was observed for the first time in this study. The mechanisms of the surface degradation process are further discussed with respect to the deformation distribution in the vicinity of the contact area under different loads.